Study on kinetics of pyrolysis reaction (degradation) of rice husk, corn cob and sugarcane bagasse as agricultural residues in Vietnam - Viet Quoc, Dinh; Son Tho, Van Dinh (Vietnam Journal of Science and Technology, 2017)
Thermochemical conversion of biomass has been studied extensively over the last decades. For the design, optimization and modeling of thermochemical conversion processes, such as fixed bed pyrolysis, a sound understanding of pyrolysis is essential. In this study, the thermal degradation of different agricultural residue species as rice husk (RH), corn cob (CC) and sugarcane bagasse (SGB) has been investigated using thermo-gravimetric. The kinetic parameters of three agricultural in the inert atmosphere are also calculated by Flynn-Wall-Ozawa method (FWO) and compared with acacia wood’s one. The average activated energy of rice husk lower than activated energy of acacia wood. The average activated energy of corn cob and sugarcane bagasse are higher than the activated energy of acacia wood thermal degradation. This result has important role in the reactor design for using agricultural residue to generate power such as pyrolysis or gasification